OPTIMALISASI STRATEGI BRANDING DALAM MENINGKATKAN BRAND IMAGE SD MA’ARIF PONOROGO - Heriyudanta, Muhammad; Heri, Muhammad Heriyudanta; Putri, Weni Tria Anugrah (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2025)
This study aims to analyze in-depth how SD Ma'arif (Small Elementary School) develops its brand image to gain public trust. The research approach is qualitative, employing a phenomenological paradigm, using a case study approach. Data sources include the principal, the vice principal for public relations, and a team of teachers and education staff appointed as the school's development team. Data collection techniques include participant observation, in-depth interviews, and documentation. The analysis technique utilizes the concepts of Miles, Huberman, and Saldana: data condensation, data presentation, and drawing conclusions or verification. The study concluded that SD Ma'arif Ponorogo does not employ a diverse strategy for building its brand image in the eyes of the public. However, it emphasized that it performs all its duties to the fullest extent possible. These include promoting the school during the PPDB (Enrollment Admission) period and proceeding appropriately, maintaining and fostering the school's identity, and consistently upholding the quality of its education